A broadcast-capable WDM passive optical network using offset polarization multiplexing - Zhong, Wende (2013)
We propose and demonstrate a wavelength-division-multiplexed passive optical network providing both unicast and broadcast services using an offset polarization multiplexing technique. The downstream differential phase-shift keying (DPSK)-formatted unicast and broadcast signals are offset polarization-multiplexed at the central office and demultiplexed and detected at the optical network units without resorting to any polarization tracking. A portion of the offset polarization-multiplexed downstream signals is fed into a polarization-sensitive weak-resonant-cavity Fabry-Perot laser diode for upstream remodulation without any polarization control. Successful transmissions of 10-Gb/s downstream unicast and broadcast DPSK signals as well as 2.5-Gb/s upstream ON-OFF keying signal over a 20-km standard single-mode fiber are experimentally demonstrated. The robustness of the proposed scheme against polarization fluctuation along the link, relative bit delay between the unicast and broadcast signals, frequency deviation of the downstream signals from the delay interferometer (DI), and imperfection of the DI is investigated.